KONTRAKT SPÓŁKI JAKO PODSTAWA ODPOWIEDZIALNOŚCI IN SOLIDUM W PRAWIE RZYMSKIM - Służewska, Zuzanna (Zeszyty Prawnicze, 2017)
THE CONTRACT OF PARTNERSHIP AS A BASE OF IN SOLIDUM LIABILITY IN ROMAN LAW Summary In the modern civil law joint and several liability of partners in a partnership is a rule rather than an exception. According to the common opinion this concept did not originate in the Roman law but was first invented in the medieval times by glossators and commentators. The Roman partnership created only a private relation between partners (who, due to a conclusion of that contract were reciprocally obliged to act together in accordance with a good faith in order to conduct common business and to divide profits and bear losses in proportion to their respective shares) and its conclusion did not affect their liability against third parties. The partners had no right to bind themselves contractually to any third parties, unless they all acted jointly (in this case, however, their joint representation was derived from their expressed declarations and not the existence of a contract o f partnership). Thus, any commitment made by an individual partner, even if made within the scope of a partnership having obtained other partners’ consent, was treated as a personal debt of this partner and the remaining partners were not liable against his contractor. Then, of course, the partner who made a commitment (acting within the partnership’s business) could claim a part of what he had paid to a third party from other partners in proportion to their respective shares in the common enterprise. Such a solution was necessary because of the purely consensual character o f the Roman partnership and the lack of any formal procedure of its conclusion and dissolution. The existence of that contract could not affect the model of the external liability of partners, because it would be too risky for third parties, which had no possibility to make sure if a contract of partnership between some persons had been actually concluded or not. Thus, the role of a contract of partnership in the Roman law was only limited to determine a mutual liability o f partners, to specify their respective rights and obligations and to define the scope of their liability against other partners. There are only a few written sources concerning so called specific kinds of partnership characterized by untypical joint and several responsibility of partners. Moreover these texts are not very clear and are difficult to interpret, so the issue of specific kinds of a partnership is a matter of doubts among Romanists. Some authors even believe that the specific types of partnership did not exist in the Roman law at all. It should be firstly observed that the texts regarding a contract of partnership itself (the texts included in the title pro socio of Justinian’ Digest) did not raise the question of the external liability of partners because they were devoted to internal settlement o f accounts within sociu Thus, taking into account only these texts one cannot ascertain that a conclusion of a contract of partnership could not affect in any way the model of the partners’ liability against third parties. Secondly, the other texts concerning the regulation of conducting an economic activity in the Roman law (actio institoria, actio exercitoria and actio de peculio) present some regularity in an introduction of joint and several liability of debtors. On the one hand that model of the liability was introduced in situations in which protecting safety of trade required that the creditor be able to claim a whole amount o f the debt from one person only. On the other hand this model of liability could be introduced only in these cases in which some internal relation existed between several debtors. On the grounds of such relations the debtor who satisfied in full the creditor’s claim could sue other debtors in order to recover their respective parts in the debt. In the Roman law that internal relation that guaranteed the possibility of a recourse could be either a joint-ownership or a partnership. Having considered that, one may say that the texts concerning specific kinds o f partnership do not prove existence of any special type of societas. These sources regard only the situations when a joint and several liability between several debtors was introduced because it was justified by the circumstances: that is the necessity to protect the safety of trade on one hand and the existence of the contract of partnership that guaranteed a possibility to realize the recourse, on the other. In conclusion one may say that although a closing of a contract of partnership did not create a joint and several liability of partners, in some cases its existence was decisive for introducing this model of liability since it guaranteed to every party a possibility to act against the others to obtain the recourse. Thus, Roman jurisprudence made an important step towards the future introduction o f joint and several liability of partners as a rule of a civil law.